2001
DOI: 10.1303/aez.2001.387
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of nematode damage by root colonization with arbuscular mycorrhiza (Glomus spp.) in tomato-Meloidogyne incognita (Tylenchida: Meloidogynidae) and carrot-Pratylenchus penetrans (Tylenchida: Pratylenchidae) pathosystems.

Abstract: Pot studies on the effects of mycorrhizal root colonization on plant growth and nematode reproduction in tomato-Meloidogyne incognita and carrot-Pratylenchus penetrans pathosystems were carried out. The mycorrhizal fungus Glomus mosseae did not protect tomato plants inoculated with the pathogen M. incognita when it was inoculated simultaneously with the mycorrhiza, as plants inoculated with M. incognita died before harvest. On the other hand, when tomato seedlings were inoculated with the nematode three weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 16 publications
4
31
2
2
Order By: Relevance
“…These results reflect those of Ryan et al (2003), who reported that with less than 50% of root colonization, the population of potato cyst nematodes (Globodera rostochiensis and G. pallida) was not suppressed on potato plants inoculated with the commercial product Vaminoc © (combination of three Glomus spp.). However, our results were contradictory to former reports, which established the suppression (roots and soil) of M. incognita in tomato (Grandison and Cooper, 1986;Talavera et al, 2001), M. hapla on onion (MacGuidwin et al, 1985) and on banana (Jaizme-Vega et al, 1997) with low root colonization. The difference between our results and those former studies on AMF suppressing Meloidogyne spp.…”
Section: Effect Of Amf and Meloidogyne Spp Inoculation On Yam Plant contrasting
confidence: 99%
“…These results reflect those of Ryan et al (2003), who reported that with less than 50% of root colonization, the population of potato cyst nematodes (Globodera rostochiensis and G. pallida) was not suppressed on potato plants inoculated with the commercial product Vaminoc © (combination of three Glomus spp.). However, our results were contradictory to former reports, which established the suppression (roots and soil) of M. incognita in tomato (Grandison and Cooper, 1986;Talavera et al, 2001), M. hapla on onion (MacGuidwin et al, 1985) and on banana (Jaizme-Vega et al, 1997) with low root colonization. The difference between our results and those former studies on AMF suppressing Meloidogyne spp.…”
Section: Effect Of Amf and Meloidogyne Spp Inoculation On Yam Plant contrasting
confidence: 99%
“…However, in the plants mycorrhized and further inoculated with the nematode (AMF T0 + NEM T3), those parameters did not show significant differences from the respective control treatment (NEM T3). These results did not agree with the earlier studies considering M. incognita and G. mosseae on the same host (Talavera et al 2001). The increased development of the root system three weeks after transplanting (regardless of presence or absence of mycorrhizal infection) might have affected the root penetration by juveniles, with the consequent reduction in the number of galls and final population of the nematode.…”
Section: Discussioncontrasting
confidence: 89%
“…They attack mainly the root system. As a consequence, the plant loses its capacity to take up water and nutrients, with likely reductions in the growth and yield (Talavera et al 2001). Nacobbus aberrans (Thorne) Thorne and Allen is a sendentary endoparasite that causes histological alterations to the root tissues, inducing gall formation.…”
Section: Introductionmentioning
confidence: 99%
“…Since AM fungi and RKN are all indigenous soil organisms and therefore co-exist in plant roots, the potential role of AM fungi as biocontrol agents and their protective effects on plants against RKN have been well documented Diedhiou et al 2003). Studies have shown that inoculation with AM fungi can significantly reduce RKN infestation and reproduction in some plant-nematode systems (Hol and Cook 2005) such as papaya with Meloidogyne incognita (Jaizme- Vega et al 2006), olive planting stocks with M. incognita and Meloidogyne javanica (Castillo et al 2006), tomato with M. incognita (Talavera et al 2001;Siddiqui and Akhtar 2007), pyrethrum with Meloidogyne hapla (Waceke et al 2001), Prunus rootstocks with M. javanica (Calvet et al 2001), and banana with M. javanica (Rodriguez and JaizmeVega 2005). In addition to enhancement of plant nutrition, especially P nutrition, establishment of arbuscular mycorrhizae may exert beneficial effects on plant growth though direct competition with RKN for infection sites and space, alteration of the composition of root exudates, or through activation of plant defense reactions and other mechanisms (Smith et al 1986;Azcón-Aguilar and Barea 1996;Harrier and Watson 2004;Li et al 2006).…”
Section: Introductionmentioning
confidence: 99%